Gambaran Perbedaan Kelengkapan Isi Resume Medis Pasien Rawat Inap Sebelum Dan Saat Pandemi Covid-19 Di Rumah Sakit Umum Daerah Wangaya Denpasar - Putu Fera Yanti Suhendri; Ni Made Diaris (Jurnal Yoga dan Kesehatan, 2023)
An incomplete medical resume is a very important issue because it can provide detailed information during the patient's stay in the hospital. This has an impact on the quality of medical records and services provided by hospitals. Related  on the results of interviews and observations at Wangaya Hospital there are differences in filling medical resume before and during the pandemic. In this regard, the purpose of this study is to get an overview of the completeness of inpatients medical resume before and during the pandemic at the Wangaya General Hospital Denpasar. This study applied a descriptive analytic qualitative research design with cross sectional type. Number of medical record samples that were used before and during the pandemic were 22,160 by using total sampling. The results of the interviews and the the analysis stated that the sample data in research on medical records of inpatients before the 2019 pandemic, the inpatients was 13,644 while in 2021 the research sample data was 8,516 medical records of inpatients during the pandemic, the difference of incomplete review of identification with a difference of 12%, the review of important report with a difference of 14%, the review of authentication with a difference of 8%, and the documentation review with a difference of 1%. Several contributing factors include doctors, nurses and registrars who are still delaying the return of medical records for those who have not filled them out. Based on the results of the study, it can be concluded that there were differences in the completeness of medical resumes at Wangaya Denpasar Hospital before and during the Covid-19 pandemic.